De novo assembly and annotation of the Amblyomma hebraeum tick midgut transcriptome response to Ehrlichia ruminantium infection. - David Omondi; Erich Zweygarth; Edwin Murungi; Frans Jongejan; Ard M Nijhof (Public Library of Science (PLoS), 2023)
The South African bont tick Amblyomma hebraeum is a hematophagous vector for the heartwater disease pathogen Ehrlichia ruminantium in southern Africa. During feeding, the tick's enterocytes express proteins that perform vital functions in blood digestion, including proteins that may be involved in E. ruminantium acquisition, colonization or immunity. To delineate the molecular mechanism of midgut response to E. ruminantium infection, we performed comparative analyses of midgut transcriptomes of E. ruminantium infected engorged A. hebraeum nymphs, and infected adult male and female ticks with their corresponding matched uninfected controls, before and during feeding. A total of 102,036 unigenes were annotated in public databases and their expression levels analyzed for engorged nymphs as well as unfed and partly-fed adult ticks. There were 2,025 differentially expressed genes (DEGs) in midguts, of which 1,225 unigenes were up-regulated and 800 unigenes were down-regulated in the midguts of infected ticks. Annotation of DEGs revealed an increase in metabolic and cellular processes among E. ruminantium infected ticks. Notably, among the infected ticks, there was up-regulation in the expression of genes involved in tick immunity, histone proteins and oxidative stress responses. We also observed up-regulation of glycoproteins that E. ruminantium could potentially use as docking sites for host cell entry. Insights uncovered in this study offer a platform for further investigations into the molecular interaction between E. ruminantium and A. hebraeum.